Oral health‐related quality‐of‐life scores differ by socioeconomic status and caries experience. Issue 3 (12th January 2017) - Chaffee, Benjamin W.; Rodrigues, Priscila Humbert; Kramer, Paulo Floriani; Vítolo, Márcia Regina; Feldens, Carlos Alberto
Abstract: Objectives: (i) Quantify the relative association between child dental caries experience and maternal‐reported child oral health‐related quality of life (OHRQoL); (ii) examine whether that association differed according to family socioeconomic status (SES); and (iii) explore whether absolute OHRQoL varied by family SES at similar levels of child caries experience. Methods: This study was a cross‐sectional analysis of children in southern Brazil (n=456, mean age: 38 months) participating in an existing health centre‐based intervention study. OHRQoL impact was quantified as mean score on the Brazilian Early Childhood Oral Health Impact Scale (ECOHIS) and compared over categories of caries experience (dmft: 0, dmft: 1‐4, dmft: ≥5). Adjusted ECOHIS ratios between caries categories were calculated using regression modelling, overall and within socioeconomic strata defined by maternal education, social class and household income. Results: Caries prevalence (dmft >0) was 39.7%, mean ECOHIS score was 2.0 (SD: 3.5), and 44.3% of mothers reported OHRQoL impact (ECOHIS score >0). Increasing child caries experience was associated with worsening child and family quality of life: ECOHIS scores were 3.0 times greater (95% CI: 2.0, 4.4) for children with dmft ≥5 vs dmft=0, a pattern that persisted regardless of family socioeconomic status ( P for interaction: all >0.3). However, adjusted for dental status and sociodemographic characteristics, mean ECOHIS scores were lower when reported by mothers of less educational attainment (ratio: 0.7; 95% CI: 0.5, 1.0), lower social class (ratio: 0.7; 95% CI: 0.5, 1.0) or in lower income households (ratio: 0.8; 95% CI: 0.6, 1.3). Conclusion: Dental caries was associated with negative child and family experiences and lower OHRQoL across all social groups; yet, families facing greater disadvantage may report lesser quality‐of‐life impact at the same level of disease experience. Thus, subjective quality‐of‐life measures may differ under varying social contexts, with possible implications for service utilization, evaluating oral health interventions, or quantifying disease morbidity in low‐SES groups.